Mafic Volcanic and Subvolcanic Rocks from the Yüksekova Complex in the İcme-Kesikköprü Province (East of Elazi?, Eastern Turkey): Whole-Rock Geochemistry and Confocal Raman Spectroscopy Characterization - Ural, Melek; Deniz, Kiymet; Sayit, Kaan (Institute of Physics Publishing, 2019)
The Late Cretaceous Yüksekova Complex within the southeastern Anatolia orogenic belt consists of mafic volcanic and subvolcanic rocks representing oceanic crustal products, which are the main focus of this study. The studied mafic lithologies from the İcme-Kesikköprü province east of Elazi? are characterized by a primary mineral assemblage of olivine, pyroxene, and plagioclase, and mainly display porphyric, intergranular, intersertal, vesicular, and amygdaloidal textures. Based on Raman peak positions, the pyroxenes of these mafic lithologies from Aşa?i Igme, Pirimezartepe and Yolüstü were determined as augite. The studied mafic rocks are chemically classified as basalt and display tholeiitic-calc-alkaline transitional characteristics. In spider diagrams, they show prominent negative Nb anomalies, while their chondrite-normalized rare earth element patterns are LREE-depleted to almost horizontal [(La/Sm)N: 0.54-1.42, (La/Lu)N: 0.54-1.85]. The immobile trace element systematics suggests that these mafic volcanic and subvolcanic rocks have originated from a metasomatized mantle source fluxed by slab-derived fluids/melts. Overall geochemical features are consistent with their generation in an oceanic arc environment. © Published under licence by IOP Publishing Ltd.
5th World Multidisciplinary Earth Sciences Symposium, WMESS 2019 -- 9 September 2019 through 13 September 2019 -- Prague -- 155452
Keywords: Earth sciences; Exploratory geochemistry; Feldspar; Rare earths; Textures; Trace elements; Volcanoes; Confocal Raman spectroscopy; Eastern Turkey; Geochemical features; Immobile trace elements; Late cretaceous; Mineral assemblage; Spider diagrams; Whole-rock geochemistries; Volcanic rocks